Three-Dimensional Modeling and In Silico Kinematic Evaluation of Interspinous Ligament Desmotomy in Horses - Biedrzycki, Adam Henry; Elane, George Louis (Frontiers in Bioengineering and Biotechnology, 2022)
Background Interspinous ligament desmotomy (ISLD) has been shown to improve comfort of horses diagnosed with overriding dorsal spinous processes (DSP), but its effects on spine mobility are unknown. Objective: To objectively quantify the change in mobility of thoracic vertebrae following ISLD using CT and medical modeling software. Study design: Prospective cadaveric manipulation of seven equine thoracolumbar spines, collected from T11-L1. Methods: Spines were collected from T11-L1 with the epaxial musculature intact. Flexion and extension phases were achieved with a ratchet device calibrated to 2000N. Bone volume CT scans were performed in resting, flexion, and extension phases. Interspinous ligament desmotomy was performed at each intervertebral space (n=8), and bone volume CT imaging was repeated for each phase. Spinal sections were individually segmented and imported into medical software for kinematic evaluation. T11 of each phase were superimposed, the distance between each DSP, the total length of the spine, and the maximal excursion of L1 along with angular rotational information were recorded. Results: Mean distance between each DSP increased by 5.6 +/- 4.9mm, representing a 24% +/- 21% increase in mobility following ISLD. L1 dorsoventral excursion increased by 15.3 +/- 11.9mm, craniocaudal motion increased by 6.9 +/- 6.5mm representing a 47% +/- 36.5% and 14.5 % +/- 13.7% increase respectively. Rotation of L1 about the mediolateral axis increased by 6.5 degrees post-ISLD. Conclusion and Clinical Relevance: ISLD increases dorsoventral, craniocaudal, and rotational motion of the equine spine. The computer modeling methodology used here could be used to evaluating multiplanar spinal kinematics between treatments.